Hippasteria californica Fisher 1905 ... - Mah, Christopher L. (Zenodo, 2016)
Hippasteria californica Fisher 1905 Fisher 1905: 310; 1911: 233; H.L. Clark 1913: 194; Alton 1966a: 1702; Lambert 1978b: 62; Maluf 1988: 34, 118; Mah et al. 2010: 285; Clark & Jewett 2011: 53. (In key as H. californica); Imaoka et al., 1991: 52 (as Cryptopeltaster lepidonotus) Comments. Hippasteria californica was observed by Fisher (1911) and Alton (1966a) to occur in a deeper bathymetric range than H. phrygiana (as H. spinosa). Further collections show this species as widely occurring from Japan to Baja California in waters as deep as 2373 m. Hippasteria californica occurs in a much deeper bathymetric range relative to H. phrygiana. Surprisingly, some shallow water members of this clade were recorded from British Columbia (Mah et al. 2014). Molecular phylogeographic data shows this species as closely related to the widely occurring H. phyrigana (Foltz et al. 2013, Mah et al. 2014). Occurrence. Gulf of California (Baja), Southern California, Washington to British Columbia, Aleutian Islands (Alaska) to ... : Published as part of Mah, Christopher L., 2016, Deep-sea (> 1000 m) Goniasteridae (Valvatida; Asteroidea) from the North Pacific, including an overview of Sibogaster, Bathyceramaster n. gen. and three new species, pp. 101-141 in Zootaxa 4175 (2) on page 117, DOI: 10.11646/zootaxa.4175.2.1, http://zenodo.org/record/257286 ...